Sexual selection drives the evolution of male wing interference patterns - Hawkes, M. F. (Proc Biol Sci, 2019)
The seemingly transparent wings of many insects have recently been found to display unexpected structural coloration. These structural colours (wing interference patterns: WIPs) may be involved in species recognition and mate choice, yet little is known about the evolutionary processes that shape them. Furthermore, to date investigations of WIPs have not fully considered how they are actually perceived by the viewers' colour vision. Here, we use multispectral digital imaging and a model of Drosophila vision to compare WIPs of male and female Drosophila simulans from replicate populations forced to evolve with or without sexual selection for 68 generations. We show that WIPs modelled in Drosophila vision evolve in response to sexual selection and provide evidence that WIPs correlate with male sexual attractiveness. These findings add a new element to the otherwise well-described Drosophila courtship display and confirm that wing colours evolve through sexual selection.